A STUDY TO FIND OUT THE FEASIBILITY OF USING SAME ABILITY GROUPING TO MINIMIZE THE PROBLEMS OF STUDENT HETEROGENEITY IN LEARNING AND TEACHING OF ENGLISH LANGUAGE IN MOTHER TONGUE MEDIUM EDUCATION - Perera, D.S.N. (My University, 2004)
Teaching English as a second language to all Sri Lankan school children has been a major educational policy of successive governments in Sri Lanka since the early 1950s, especially to equip students for the modern job market. Yet, the continued low pass rate at the G . C . E (O/L) Examinations through out the past years bears evidence to its utter failure. One principle factor that has led to the ineffectiveness of the Learning and Teaching of English as a second language, as identified by many researchers, is the student heterogeneity in our public school classrooms. Due to nationalization o f schools which enabled the access of schools to everybody, students who had not studied English earlier found themselves in the same class with those who knew English and spoke the language at home. This study attempts to identify the problems faced by both students and teachers when learning and teaching English in such heterogeneous or mixed ability classrooms. It also attempts to suggest ways to minimize the identified problems, through the approach of Same ability grouping for the purpose of Learning and 'teaching of English as a second language in our schools. The problems relating to student heterogeneity were identified through questionnaires administered to teachers and students of mixed ability classes. Through the case study of a school which carried out such a policy of grouping, for the purpose of teaching English the researcher was able to find out how much such an approach affected the students psychologically, academically and socially and whether they accept and value such a system as beneficial and whether it increases the student achievement or whether it unfairly labels them. The questionnaire data indicated that most students were appreciative of their ability grouping even though many are very much concerned about the labelling. Even the less proficient learners are comfortable and are free to interact in their groups. Therefore the results indicated positive language acquisition. The teachers too were of the opinion that ability grouping could solve some of their problems as they were free to adjust instruction according to the levels of the students.